Strategi Pelatihan Penginovasian Kerajinan Anyaman Pandan Guna Meningkatkan Komunitas Standar Produk di Pemasaran Mancanegara - Widyanani Widyanani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The problem to be discussed in this research is to find out the training strategy for innovation of pandan weaving to increase the product standard community in overseas marketing as well as the marketing strategy for innovation of pandan weaving to increase the product standard community in international marketing. The research method used in this research is a qualitative method with a descriptive approach. . The research results that have been found in this research are: 1). Organizing Innovation Training on Pandan Woven to improve community product standards in international marketing is: a. Selection of Raw Materials b. Cutting, slicing, forming c. Weaving and forming innovation d. The final stage is the finishing process which is the final process from which the previous stages have been completed. The raw model of pandan that has become tanned can be seen in terms of shape, quality of workmanship as well as physical appearance or finishing. 2. Marketing Strategy Innovation of pandan woven to improve product standard communities in international marketing, namely: 1) Needs, Demands and Desires. 2) Satisfaction, value, products and costs, where the fulfillment of needs and desires must have a relationship with products and services. 3) Transactions, Relationships, and Exchanges. and 4) Marketers, marketing and markets, marketing via social media will influence external factors that influence consumer perceptions of a product, which will then influence consumer buying interest.